Smart sensor node of wireless sensor networks (WSNS) for remote river water pollution monitoring system - Kadir, E.A. (Springer Singapore, 2020)
Indonesia is one of the countries that have many rivers and lakes. It is situated, in South East Asia and enjoys tropical climate all year round. Riau province is located in the centre and middle of Sumatera Island which in the heart of Sumatera. This province has more than five big rivers that are used by the community every day for their daily activities. The rapid economic development has significant impact to the region where many industries operating along the river produce industrial wastes that pollutes the river water. This chapter discusses the development of river water monitoring system where several relevant parameters are monitored. The Wireless Sensor Networks (WSNs) used in this study integrates a sensor node that is attached to multiple sensors such as water temperature, pH, dissolved oxygen (DO) and electrical conductivity. The monitoring system is specially designed to be able to monitor water level and flow rate for environmental and flood alert purposes. A sensor node collects information from the multiple sensors and forwards to the WSNs sink node which embedded with a microcontroller unit and memory as local database before sending signals to the backend system. The backend system displays vital information that can be monitored by institutions or local authorities. Prompt action will be can be taken if abnormality is raised by the monitoring system. A prototype of this WSNs node has been designed and tested, the results shows that sensor node is reliable for the detection of polluted water parameters, water levels as well as river flow rate. Furthermore, sensor node was tested at one of the rivers in Riau Province, Indonesia to compare results with actual river water. All the data were keep in the database for recording of analysis and for future development of monitoring system. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2020.